Kesan arahan tumpuan terhadap aktiviti otot dan prestasi semasa senaman squat - Nor Fazila Abd Malek (Tanjong Malim, 2020)
Kesan arahan tumpuan terhadap aktiviti otot dan prestasi semasa senaman squat by Nor Fazila Abd Malek